Inosine enhances the efficacy of immune‐checkpoint inhibitors in advanced solid tumors: A randomized, controlled, Phase 2 study - Haiqing Zhao; Wei Zhang; Yuting Lu; Yin Dong; Zhihao He; Hongchao Zhen; Qin Li (Cancer Medicine)
Abstract Background This study aimed to evaluate whether inosine enhances the efficacy of immune‐checkpoint inhibitors in human malignant solid tumors. Methods This single‐center, prospective, randomized, open‐label study was conducted, from January 2021 to December 2022, in Beijing Friendship Hospital, Capital Medical University, and participants were randomly assigned (1:1) to either the inosine (trial) or non‐inosine (control) group that received inosine (dosage: 0.2 g, three times/day) + PD‐1/PD‐L1 inhibitor or only PD‐1/PD‐L1 inhibitor ± targeted ± chemotherapy, respectively. Efficacy was assessed every 6 weeks (i.e., after every two–three treatment cycles). The primary endpoint was the objective response rate (ORR); the secondary endpoints were disease control rate, overall survival (OS), and progression‐free survival (PFS). The trial was registered at ClinicalTrials.gov (NCT05809336). Results Among the 172 participants with advanced malignant solid tumors, 86 each were assigned to the inosine and non‐inosine groups, wherein the median PFS (95% CI) was 7.00 (5.31–8.69) and 4.40 (3.10–5.70) months, respectively (hazard ratio [HR] 0.63; 95% CI 0.44–0.90, p = 0.011), and the ORR was 26.7% and 15.1%, respectively (p = 0.061). In the inosine and non‐inosine groups, the median OS was not reached and was 29.67 (95% CI 17.40–41.94) months, respectively (HR 1.05 [95% CI 0.59–1.84], p = 0.874). Compared with the non‐inosine group, the median PFS and ORR of the inosine group were significantly prolonged and improved in the multiple exploratory subgroup analyses. The safety analysis showed that Grades 3 and 4 adverse reactions occurred in 25 (29%) and 31 (36%) patients in the inosine and non‐inosine groups, respectively, and tended to decrease in the inosine group compared with the non‐inosine group. Conclusion Inosine had a tendency to enhance the efficacy of immune‐checkpoint inhibitors and reduced immunotherapy‐related adverse reactions.